Numerical simulation of metal removal in laser drilling using radial point interpolation method. (April 2017) - Abidou, Diaa; Yusoff, Nukman; Nazri, Nik; Omar Awang, M.A.; Hassan, Mohsen A.; Sarhan, Ahmed A.D.
Abstract: Prediction of penetration depth in metal laser drilling is done through a simple meshfree numerical model. 2D axisymmetric simplified model of transient metal laser drilling is proposed for continuous laser beam of Gaussian distribution with strong form of Radial Point Interpolation Method (RPIM) used for approximating the temperature field. The commonly used Multi-Quadrics (MQ) and Exponential (EXP) Radial Basis Functions (RBFs) are tested and compared with each other. The model logic is constructed in MATLAB code, while the results are compared with published numerical and experimental work. The simulation results give good agreement with the previous numerical and experimental work, showing the model reliability in predicting the penetration depth in such a physically complex process.